Effect of different fertilizers on the physicochemical properties, chemical element and volatile composition of cucumbers. (15th January 2022) - Mi, Si; Zhang, Xiangnan; Wang, Yuhang; Ma, Yuedong; Sang, Yaxin; Wang, Xianghong
Highlights: Chemometrics was applied to investigate the effect of different fertilizers. The co-use of chicken manure and NPK fertilizer showed the best texture quality. The addition of microbial fertilizer at 6000 kg/ha improved the color quality. No fertilizer treatment facilitates the accumulation of most elements in cucumbers. The addition of microbial fertilizer enhanced the volatile profiles of cucumbers. Abstract: The main purpose of the present study was to investigate the effect of different fertilizers on the physicochemical properties, multi-element and volatile composition of cucumbers. All samples were divided into five groups according to different combinations and amounts of chicken manure, NPK 17-17-17 fertilizer and microbial fertilizer. The co-application of chicken manure (120, 000 kg/ha) and NPK 17-17-17 fertilizer (750 kg/ha) achieved the best texture properties, whereas the addition of the microbial fertilizer at 6000 kg/ha significantly improved the color quality of cucumbers. Similarly, the co-application of chicken manure, NPK 17-17-17 fertilizer and microbial fertilizer at 6000 kg/ha enhanced the number and abundance of volatile components detected in the cucumbers. Cucumbers from the control group contained the highest levels of most of the determined elements. Overall, a combination of chicken manure, NPK 17-17-17 fertilizer and 6000 kg/ha microbial fertilizer is recommended as a relatively efficient fertilizer utilization for cucumbers.